3D Printing in the Wild: Adopting Digital Fabrication in Elementary School Education. (25th June 2020) - Leinonen, Teemu; Virnes, Marjo; Hietala, Iida; Brinck, Jaana
Abstract: In recent years, digital fabrication, and especially its associated activities of 3D design and printing, have taken root in school education as curriculum‐based and maker‐oriented learning activities. This article explores the adoption of 3D design and printing for learning by fourth, fifth and sixth grade children (n=64) in multidisciplinary learning modules in elementary school education. School‐coordinated 3D projects were not led by design experts, such as art and design teachers, designers, researchers or technical specialists, but run 'in the wild' by school teachers. The study was conducted by using an ethnographic research design, including field observations, non‐formal interviews and a reflective questionnaire. The results indicate that, in the adoption of 3D printing activities, learning is centred on the technical skills and the usage of 3D tools. Hence, the elementary ABCs of 3D printing do not achieve the full design and creativity potential of digital fabrication that earlier research has suggested. However, the results do have implications for the potential of 3D printing projects to increase children's empowerment. In their current state, 3D design and printing are some of the learning tools, among others, and similar achievements can be achieved with other hands‐on learning technologies. In order to enhance the learning of creativity and design thinking skills, 3D activities in school should be planned accordingly.